An integrated technology-supported platform for reminiscence therapy - Haron, Haryani; Md Sabria, Sabiroh; Che Ali, Maryani (2016)
The reminiscence therapy, a process of remembering, have been proven to be an effective method in enhancing the cognitive capacities of the elderly. The use of new technology by the elderly population is being widely accepted for having a beneficial effect on their quality of life, also pave ways for the usage of technology to support the reminiscence therapy. Our study focus on exploring elderly reminiscence therapy and proposed suitable technology that can support reminiscence therapy process and make the whole process more practical and manageable.Two factors were found to be the determinant of the reminiscence therapy i.e. the participant’s cognitive level and the type of provider. Besides that, we also discovered that reminiscence therapy consists of processes which could be supported by technologies.Thus, the development of technology supported framework which comprises of multimedia technology, collaborative technology and repository system, supported the reminiscence therapy process, leading to more practical and manageable reminiscence therapy.The contribution of this study towards new knowledge is through the development of an integrated technology-supported platform which was designed based on the real practice of reminiscence therapy.The prototype of the system is currently being developed and will contribute towards practice.